Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae) - Kodada, Ján; Sangpradub, Narumon; Somnark, Rungnapa; Gruľa, Daniel; Žiak, Dávid; Freitag, Hendrik (Zootaxa, 2017)
A new species of riffle beetle, Vietelmis jablonskii, from Laos and Thailand is described and illustrated. Differences to other Vietelmis species are discussed and an identification key for the Vietelmis is presented. New faunistic records are provided for V. kovaci Kodada & Čiampor, 2000; the genus Vietelmis is newly recorded for Thailand.